Real-time Multi-Level Wireless Control Model based on IoT for Wheeled Robots - Rahmani, Budi; Alfarisi, Ajib; Ilmi, Ilmi; Miftahuddin, Miftahuddin; Wahyudi, M Agus; Melyana, Melyana; Mahrita, Mahrita (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2023)
Demands regarding a wireless control system for all-wheeled soccer-playing robots in the 2023 Indonesian robot contest require significant changes to the STMIK Banjarbaru's robot design. Therefore, the team designed and tested the robot control program using an ATMega2560 microcontroller and a laptop on top of the robot. The wheeled robot used another laptop as a controller outside the robot. This research reprogrammed the soccer player's wheeled robot prototype from the microcontroller controller side regarding the robot's movement using a holonomic model. Then, the microcontroller is programmed to receive commands to move the robot from the laptop installed on the robot via serial communication with a USB cable. This study also created an application in the form of a GUI (Graphical User Interface) on the laptop on the robot. Then, it is also ready to be controlled wirelessly from the laptop outside the robot. The test results show that this research has overcome the main problems related to response time and consistency in carrying out essential motor functions, including forward, backward, sliding, and rotating movements on the robot. Additionally, this experiment successfully met the challenges of performing specialized functions such as motor dribbling and ball kicking with a significant level of success. Wireless test results using access point frequencies of 2.4 GHz and 5.8 GHz also produced exemplary achievements, demonstrating the robot's ability to communicate efficiently in various environments.Keywords: ATMega2560 microcontroller; Robot; Holonomic; Wireless control; Response timeÂ AbstrakTuntutan terkait sistem kendali nirkabel atas semua robot beroda pemain bola di kontes robot Indonesia tahun 2023 menuntut perubahan signifikan terhadap rancangan robot oleh tim di STMIK Banjarbaru. Karenanya tim telah merancang bangun sekaligus mengujicoba program pengendali robot menggunakan mikrokontroler ATMega2560 serta laptop yang diletakkan di atas robot. Selain itu juga digunakan laptop lain sebagai pengendali di luar robot. Adapun yang dilakukan adalah dengan memrogram ulang prototipe robot beroda pemain bola dari sisi pengendali mikrokontroler terkait gerakan robot dengan model holonomic. Kemudian Mikrokontroler diprogram untuk juga bisa menerima perintah menggerakkan robot dari laptop yang dipasang di robot melalui komunikasi serial dengan kabel USB. Selanjutnya, pada laptop yang ada di robot dibuatkan aplikasi berupa GUI (Graphical User Interface) untuk kemudian juga siap dikendalikan secara nirkabel dari laptop di luar robot. Hasil pengujian menunjukkan bahwa penelitian ini berhasil mengatasi permasalahan utama terkait waktu respon dan konsistensi dalam menjalankan fungsi motorik dasar, termasuk pergerakan maju, mundur, geser, dan berputar pada robot. Selain itu, eksperimen ini berhasil menghadapi tantangan dalam menjalankan fungsi khusus seperti motor drible dan penendang bola dengan tingkat keberhasilan yang signifikan. Hasil pengujian nirkabel menggunakan frekuensi akses poin 2.4 GHz dan 5.8 GHz juga menghasilkan pencapaian yang baik, menunjukkan kemampuan robot untuk berkomunikasi secara efisien dalam berbagai lingkungan.Â